One Great Family Domestic Relationships in Samuel Richardson's Novels - Höhn, Simone Eva (Schweizer Anglistische Arbeiten / Swiss Studies in English, 2020)
This study examines concepts of morality and structures of domestic relationships in Samuel Richardson's novels, situating them in the context of eighteenth-century moral writings and reader reactions. Based on a detailed analysis of Richardson's work, this book maintains that he sought both to uphold hierarchical concepts of individual duty, and to warn of the consequences if such hierarchies were abused. In his final novel, Richardson aimed at a synthesis between social hierarchy and individual liberty, patriarchy and female self-fulfilment. His work, albeit rooted in patriarchal values, paved the way for proto-feminist conceptions of female character.